1999
DOI: 10.1074/jbc.274.32.22127
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the TFIIH XPB DNA Helicase in Promoter Escape by RNA Polymerase II

Abstract: TFIIH is an RNA polymerase II transcription factor that performs ATP-dependent functions in both transcription initiation, where it catalyzes formation of the open complex, and in promoter escape, where it suppresses arrest of the early elongation complex at promoter-proximal sites. TFIIH possesses three known ATPdependent activities: a 3 3 5 DNA helicase catalyzed by its XPB subunit, a 5 3 3 DNA helicase catalyzed by its XPD subunit, and a carboxyl-terminal domain (CTD) kinase activity catalyzed by its CDK7 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 43 publications
3
72
0
Order By: Relevance
“…In previous studies (3,4,6,25), efficient promoter escape by RNA polymerase II was shown to depend strongly on the TFIIH XPB DNA helicase, an ATP(dATP) cofactor, and a region of promoter DNA extending Ϸ39-50 bp downstream from the transcriptional start site. In addition, we showed that transcription initiation by RNA polymerase II depends on a region of promoter DNA extending Ϸ23-39 bp downstream from the transcriptional start site when initiation depends on TFIIH and an ATP(dATP) cofactor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies (3,4,6,25), efficient promoter escape by RNA polymerase II was shown to depend strongly on the TFIIH XPB DNA helicase, an ATP(dATP) cofactor, and a region of promoter DNA extending Ϸ39-50 bp downstream from the transcriptional start site. In addition, we showed that transcription initiation by RNA polymerase II depends on a region of promoter DNA extending Ϸ23-39 bp downstream from the transcriptional start site when initiation depends on TFIIH and an ATP(dATP) cofactor.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the TFIIH XPB DNA helicase functions at multiple steps to promote efficient transcription initiation and promoter escape by RNA polymerase II. The TFIIH XPB DNA helicase catalyzes ATP(dATP)-dependent formation of the open complex before synthesis of the first phosphodiester bond of nascent transcripts (2), and it is required to suppress premature arrest of very early RNA polymerase II elongation intermediates at promoterproximal sites Ϸ10-12 bp downstream of the transcriptional start site before their escape from the promoter (3)(4)(5).…”
mentioning
confidence: 99%
“…DNA helicases necessary for the initiation of transcription have been well defined. These helicases include the subunits of the transcription factor IIH complex, which specifically interact with RNA Pol II complex on the promoter (34,35). The DNA helicase involved in transcription elongation has remained a mystery.…”
Section: Discussionmentioning
confidence: 99%
“…TFIIH consists of nine subunits including excision repair cross-complementing (ERCC) 3 (XPB), ERCC2 (XPD), and MO15, which have 3Ј-5Ј helicase, 5Ј-3Ј helicase, and C-terminal domain kinase activities, respectively (19,20). Both promoter opening and promoter escape require the ERCC3 helicase activity and (d)ATP hydrolysis (21,22), which can be circumvented by the negative supercoiling of the template DNA (18). In addition to the role in basal transcription, TFIIH is critically important for activated transcription.…”
mentioning
confidence: 99%